Enhancing the Power Conversion Efficiency of Inverted Organic Photovoltaics with Gold Functionalized Reduced Graphene Oxide. Issue 1737 (11th June 2015) - Isseroff, Rebecca; Yang, Zhenhua; Kim, Jessica; Chen, Andrew; Rafailovich, Miriam
ABSTRACT: In this study, an "inverted" design, phase-separated morphology and gold-functionalized reduced graphene oxide (Au-rGO) were used to address exciton recombination and poor Fermi level alignment. To increase efficiencies, a unique methodology was used to coat Au-rGO on top of the active layer. When 0.05 Au-rGO was blended with the active layer, there were metal-thiolate bonds with P3HT and π-π stacking with PCBM. However, KPFM, measured for the first time for this material, showed that the while 0.05mM Au-rGO reduced the energy gap between P3HT and PBCM, this was offset by recombination. KPFM showed that Au-rGO may be better suited between the active layer and electrode. When 0.5mM Au-rGO was coated on top of the active layer, efficiency increased (p<0.002) nearly 600%, suggesting that Au-rGO is a more effective acceptor than a constituent of the active layer.